Virtual Socialization Through Online Game: Social Interaction in Roblox - Syakilah Azzahra; Najwa Naela Putri; Asyrof Bahauddin Mubarok; Khomarudin Khomarudin (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
Online games, especially on the Roblox platform, have become an increasingly significant digital interaction environment. This study aims to explore social interactions in the context of online gaming, with a particular focus on the Roblox platform. Roblox was chosen as the research subject due to its growing popularity and the diverse and complex social environment it offers. A qualitative approach was employed, with data collected through direct observation within the game, allowing for firsthand observation of player interaction dynamics. Additionally, a sample of Roblox players was surveyed using a questionnaire containing several questions related to interaction and socialization. The collected data were then analyzed by identifying key themes related to the game's influence on friendship-building, collaboration, and emerging communication norms within the gaming community. As a result, player interactions in the online gaming environment have implications for creating inclusive online communities and designing games that enhance players' social experiences. Keywords: Social interaction, Online gaming, Roblox